(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The assessment of clinical indices following induction and maintenance of anaesthesia using two different combinations of Romifidine/Ketamine was done in donkeys. Six donkeys, 3-5 years of age with average body weight of 90±15 kg, were used in the study. Each animal was anaesthetized with one of two different protocols with two weeks’ interval between each successive injection as washing out period. In the first protocol, donkeys were premedicated with 100mg/kg Romifidine (IV) and then after 10 minutes donkeys were injected with 4mg/kg ketamine intravenously for induction of anaesthesia (RK). In the second protocol, animals were treated as above and then anaesthesia was maintained immediately by intravenous infusion with ketamine 6mg/kg and romifidine100mg/kg in saline drip (RKI). Clinical indices: respiratory rate, heart rate and rectal temperature were monitored before, during and following induction of anaesthesia. Some blood biochemical parameters: urea, glucose, alanine trasaminase (ALT), and aspartate transaminase (AST) were measured before and during anaesthesia. Results obtained show that respiratory rate and rectal temperature were affected significantly (p≤0.05) as a result of using each of the two protocols. Heart rate was found to be non-significantly affected. Blood urea levels were also found to be affected significantly as a result of using the two different protocols. Glucose level, and AST and ALT activity were found to exhibit no-significant change following anaesthesia with RK or RKI. It could be concluded that the two protocols under test could be used safely in veterinary anaesthesia, although the increase in the urea level could limit the frequent or repeated usage of the two protocols on the same animal.